Ancient precepts on the tranquillity of mind - Dziurosz-Serafinowicz, Dominika (Kultura-Społeczeństwo-Edukacja, 2025)
The paper concerns Seneca’s and Plutarch’s teaching on tranquillity. These Ancient philosophers’ letters, later on called equally “On Tranquillity of Mind”, expose several issues connected with tranquil states of mind, such as reasoning and argumentations against passions, moderation between hyperactivity and apathy, the application of premeditatio malorum, making the right use of conditions, accepting the events cheerfully, avoiding lamentation, or having good companions, etc. The two sages see in philosophy a doctor helping cure the soul and share with us moral precepts on how to gain peace in mind.